Improving care experiences for premenstrual symptoms and disorders in the United Kingdom (UK): a mixed-methods approach - E. L. Funnell; N. A. Martin-Key; S. Bahn (BMC Health Services Research)
Abstract Background Poor care experiences are reported for premenstrual disorders, which may result in negative outcomes such as distress, reduced healthcare engagement, and delays to diagnosis. This research aimed to explore healthcare experiences for premenstrual symptoms in the United Kingdom and identify areas for potential improvements based on participant responses. Method An online survey was delivered, with participants recruited via social media. Experiences of care were explored using quantitative and qualitative questions. Quantitative data were explored using descriptive statistics, with group differences investigated using Mann–Whitney U tests and chi-square tests as appropriate. Qualitative data regarding care improvements was explored using inductive thematic analysis. Results The sample included 339 participants who completed at least 97% of the survey, reported premenstrual symptoms in consecutive cycles, and had sought formal help for these symptoms. Mean age was 34.66 (SD = 5.88), with the majority identifying as women (n = 332, 97.94%) and white/Caucasian (n = 311, 91.74%). 75.22% (n = 255) felt that care was poor. 44.25% (n = 150) felt their symptoms were not taken seriously. 37.76% perceived a lack of healthcare professional knowledge (n = 128). The majority did not receive recommendations of non-formal sources of help (i.e., websites, support groups; 84.96%, n = 288) or lifestyle changes (74.63%, n = 253). Better care experiences were associated with healthcare professionals taking symptoms seriously (U = 1383.00, p < .001), higher perceived healthcare professional knowledge (U = 1370.50, p < .001), and receiving recommendations of non-formal sources of help (X2 = 48.251, df = 1, p < .001, Φc = .382) or lifestyle changes (X2 = 7.849, df = 1, p = .005, Φc = .152). Thematic analysis revealed 8 aspects of care improvement: Empathetic care provision; Healthcare professional education, understanding, and research; Comprehensive symptom assessment and investigations; Diagnosis; Professional support and treatment provision; Signposting or referral to additional resources or sources of help; Wider healthcare system improvements; and Patient role/voice and preferences. Conclusions Poor care experiences for premenstrual symptoms in the UK are characterised by dismissive attitudes and perceived lack of knowledge. Improved training provision for healthcare professionals is required to address this and other aspects of care identified by qualitative analysis. However, research is needed to identify appropriate methods to deliver training. Utilisation of standardised screening tools and patient-centred communication will likely ensure comprehensive assessments and reduce self-advocacy burdens.